Comparison of mean platelet volume (MPV) and sFlt-1/PlGF ratio as predictive markers for preeclampsia. (3rd May 2021) - Mayer-Pickel, Karoline; Stern, Christina; Eberhard, Katharina; Lang, Uwe; Obermayer-Pietsch, Barbara; Cervar-Zivkovic, Mila
Abstract: Introduction: Preeclampsia is characterised by an increased platelet consumption with consecutive reduction of overall platelet count and a consecutive rise in mean platelet volume (MPV). MPV has therefore been suggested as a predictive marker for preeclampsia. We aimed to investigate MPV longitudinally in women with preeclampsia compared to healthy controls during pregnancy for potential early detection of preeclampsia and to compare potential MPV changes against the sFlt-1/PlGF ratio. Study design: This longitudinal study included 38 women with preeclampsia and 84 women with normal pregnancies, where MPV and sFlt-1 and PLGF levels were determined every 4 weeks, starting in early pregnancy. Results: MPV was significantly higher in women who developed preeclampsia compared to women with normal pregnancies at 12, ( p = .029), 24 ( p = .011), 28 ( p = .037), 32 ( p = .002), and 36 weeks of gestation, respectively ( p = .015). Further analysis revealed a cut-off point of 10.85 fl (sensitivity 65.6%, specificity 26.2%) for the prediction of preeclampsia. The sFlt-1/PlGF ratio was significantly higher in women who developed preeclampsia compared to women with normal pregnancies at the same time points ( p = .001). The cut-off point for predicting preeclampsia was 10.3 (sensitivity 87.5%, specificity 11.9%). ROC curve analysis showed that MPV has a high predictive value for early-onset preeclampsia ( p < .05) but not for late-onset preeclampsia. Conclusion: MPV is significantly elevated even in early pregnancy in women who develop preeclampsia and seems, therefore, a valuable predictor for preeclampsia even at early gestation. However, according to our results, MPV seems reliable in predicting early onset preeclampsia.